Health-System Factors Associated with the Occurrence of Stillbirths among Women Delivering in Selected Hospitals of Marsabit County - Wako, Badane; Affey, Fatuma (Journal of Health, Medicine and Nursing, 2025)
Purpose: The study sought to determine Health system factors associated with occurrence of stillbirths in selected hospitals in Marsabit County, Kenya Methodology: The study employed a cross-sectional descriptive study design, targeting 387 women who delivered in selected hospitals in Marsabit County, to collect qualitative and quantitative data. Quantitative data were analyzed using the Statistical Package for Social Sciences version 24.0 while qualitative data were analyzed using N-Vivo software version 22. Inferential statistics were calculated using Chi Square and Fisher’s Exact Tests at 95% confidence interval and P<0.05 was considered significant. Findings: The rate of stillbirth occurrence was 5.9%. Health system factors such as distance (p=0.002), cost of transport (p=0.036), health information (p=0.004), type of insurance (p=0.029) and culture (p=0.031) were significantly associated with outcome of delivery. Unique Contribution to Theory, Practice and Policy: The respondents from Marsabit County experienced relative high rates of stillbirth compared to the national figure. The outcome of delivery was significantly influenced by Health System Factors Contributing to Stillbirths Incidences in Marsabit County. These results may help address the high rate of stillbirth across the country and improve the delivery outcomes of pregnancies among mothers delivering in public hospitals.